2011
DOI: 10.1111/j.1751-7133.2011.00241.x
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Risk Scores and Patient Outcomes in Advanced Heart Failure

Abstract: Congest Heart Fail. 2011;17:205–212. © 2011 Wiley Periodicals, Inc. Significant improvements in survival have occurred for patients with advanced heart failure, with an increasing array of therapeutic options sharing quite varied properties of cost, invasiveness, and impact on life expectancy. Risk models allow patients and providers to achieve a better understanding of prognosis than is possible through unstructured holistic assessment. This article reviews scoring systems for heart failure prognostication in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 88 publications
0
17
0
Order By: Relevance
“…This multi-variable statistical analysis lead to the formation of scores used in clinical practice, providing estimation of risk for mortality ( e.g. Heart Failure Survival Score [46], Get With the guidelines score [47], Seattle Heart Failure Model [48], EFFECT [49]), re-hospitalizations [50] and morbidity [51].…”
Section: Prediction Of Adverse Eventsmentioning
confidence: 99%
“…This multi-variable statistical analysis lead to the formation of scores used in clinical practice, providing estimation of risk for mortality ( e.g. Heart Failure Survival Score [46], Get With the guidelines score [47], Seattle Heart Failure Model [48], EFFECT [49]), re-hospitalizations [50] and morbidity [51].…”
Section: Prediction Of Adverse Eventsmentioning
confidence: 99%
“…Reclassification was mainly achieved by the identification of additional high-risk individuals. In a recent review, Ketchum and Levy24 suggested that risk scores had an increasing role to play among patients with advanced heart failure whose survival has improved due to therapeutic and technological advances. They suggested that risk scores could be used to assist the selection of patients for transplantation, left ventricle assist devices and implantable cardioverter defibrillators.…”
Section: Do Biomarkers Add Value?mentioning
confidence: 99%
“…27 Moreover, the SHFM has been shown to overestimate survival among sicker patients. 28,29 Like most of the previously developed prognostic models, 30 our model was not validated in a separate cohort of patients. It was internally validated using the bootstrap method.…”
Section: Limitationsmentioning
confidence: 99%